Indigenous Health Systems and Adolescent Sexual Health in Umguza and Mberengwa Districts of Zimbabwe: Community Key Stakeholders' Perspectives - Wilfred Njabulo Nunu; Lufuno Makhado; Jabu Tsakani Mabunda; Rachel Tsakani Lebese (SAGE Publishing, 2021)
Different stakeholders play varying roles in shaping up adolescent sexual behaviours that, in turn, influence their sexual experiences. In Zimbabwe, it has been reported that adolescents from cultural districts exhibit poor sexual health outcomes as compared to other districts. Therefore, this study sought to explore the role of different key community stakeholders in the indigenous health system and how it impacts on adolescent sexual health issues. The study further explored how the indigenous health system could be integrated into the modern health system. A qualitative cross-sectional survey was conducted on purposively and snowballed respondents in Umguza and Mberengwa districts. Interviews and focus group discussions were used to gather and record data from participants. The recorded data were transcribed verbatim, translated to English, coded and thematically analysed on MAXQDA Analytics Pro 2020. Four superordinate and 12 subordinate themes emerged from the data during analysis. Stakeholders play varied roles in adolescents' upbringing and support though there are contradicting teachings from the indigenous health system and modern health system. It is possible to integrate these two systems though there were foreseen logistical challenges and clashes in the values and belief systems. Participants made suggestions on how these challenges could be overcome. There is a window of opportunity to pursue the suggested ways of integrating indigenous health systems and modern health systems for improved adolescent sexual health outcomes.